Triaxial Compression Fracture Characteristics and Constitutive Model of Frozen–Thawed Fissured Quasi-Sandstone - Yi Xie; Jianxi Ren; Tailang Caoxi; Xu Chen; Mengchen Yun (Applied Sciences, 2022)
The artificial frozen wall crossing the water-rich sand layer is prone to failure during thawing. To study the loading fracture characteristics and damage evolution of single-fissured sandstone after thawing, quasi-sandstones with prefabricated single fissure at different angles were prepared using the sandstone of the Luohe Formation as the original rock to conduct freeze–thaw tests with various temperature differences, and triaxial compression tests were performed on the samples. Based on the distribution theory of rock micro-element strength and static elastic modulus, a damage constitutive model of single-fissured quasi-sandstone under freezing–thawing and confining pressure was established. The results show that with the decrease in freezing temperature, the amount of flake spalling on the sample surface increases, and the frost-heaving cracks of quasi-sandstone become more numerous and longer, which makes the single-fissured quasi-sandstone tend to have a more complex tensile–shear hybrid failure than a shear failure. Moreover, with the increase in fissure angle, the absolute value of the freezing temperature required to produce frost-heaving cracks increases. An S-shaped damage evolution curve corresponds to each stage of triaxial compression of single-fissured quasi-sandstone. With the decrease in freezing temperature, the strength of rock after thawing decreases, and the brittleness characteristics strengthen.